2013
DOI: 10.1177/0956462413498858
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional evaluation of the prevalence and associations of HIV among female sex workers in the Gambia

Abstract: To determine HIV prevalence among female sex workers in the Gambia and HIV risk factors, we accrued participants (n = 251) through peer-referral and venue-based recruitment. Blood samples were screened for HIV and participants were administered a questionnaire. Bivariate and multivariate logistic regression identified factors associated with HIV status. Forty respondents (15.9%) were HIV-positive: 20 (8.0%) were infected with HIV-1 only, 10 (4.0%) with HIV-2 only, and 10 (4.0%) with both HIV-1 and HIV-2; 12.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
(53 reference statements)
0
27
0
Order By: Relevance
“…This study was a descriptive, cross-sectional biological and behavioral study among FSW in Lilongwe, Malawi. From July through September 2014, we systematically recruited FSW using venue-based sampling at venues where FSW are known to solicit sex (Johnston, Sabin, Mai, & Pham, 2006; Peitzmeier et al, 2014). Our outreach team comprised HIV testing counselors, interviewers, a study nurse, a driver for the mobile clinic, and a peer FSW to facilitate approaching women at the venues.…”
Section: Methodsmentioning
confidence: 99%
“…This study was a descriptive, cross-sectional biological and behavioral study among FSW in Lilongwe, Malawi. From July through September 2014, we systematically recruited FSW using venue-based sampling at venues where FSW are known to solicit sex (Johnston, Sabin, Mai, & Pham, 2006; Peitzmeier et al, 2014). Our outreach team comprised HIV testing counselors, interviewers, a study nurse, a driver for the mobile clinic, and a peer FSW to facilitate approaching women at the venues.…”
Section: Methodsmentioning
confidence: 99%
“…We employed a cross-sectional design to systematically recruit FSW using venue-based sampling, a strategy with documented success in identifying hidden populations, such as FSW. 4751 We recruited FSW using a mobile van and an outreach team comprising a peer FSW, HIV testing counselors, interviewers, a study nurse, and a driver. The mobile van was operated by TfaC and in addition to contributing to study specific activities, TfaC staff provided group sexual risk reduction and family planning counseling at the venue after study activities were completed.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis of FSW studies in low to middle-income countries indicated that FSW in sub-Saharan Africa had 12.4 times the odds of HIV compared with all women of reproductive age [15 ▪▪ ]. HIV prevalence in FSW varies within and across west African settings, with reported estimates over the past 5 years of 15.9% in The Gambia [22], 20% in Nigeria [23], 20.1% in Senegal [21], 25.7% in Bobo-Dioulasso, Burkina Faso [24], 26.6% in Côte d’Ivoire [17], 30.4% in Cotonou, Benin [25], 45.4% in Lome, Togo [20] and up to 68.6% in a study in Ghana and Benin [18] (Table 1). Although data are scarce for male and transgender sex workers, a study conducted among male sex workers in Côte d’Ivoire identified an HIV prevalence of 50% [7].…”
Section: Concentrated Epidemicsmentioning
confidence: 99%